La battaglia di Adua secondo Cerulli Etiopico 318 - Raineri, Osvaldo (Aethiopica, 1998)
This article: “La battaglia di Adua secondo Cerulli Etiopico 318” (“The Battle of Adwa according to Cerulli Etiopico 318”) on the unpublished Ethiopian text (Geʿez) and Italian translation is an extended version of my contribution to the Adwa Victory Centenary Conference (26th February - 2nd March, Addis Ababa - Adwa, Ethiopia). It represents a short account of the reign of Menelik (1889 - 1913), which for the main part of its contents, is dedicated to the war led by the Ethiopian sovereign against the Italians, with particular emphasis on the Battle of Adwa.